THE IMPACT OF SOCIAL MEDIA ON THE GLOBAL SPREAD OF ENGLISH - Kuziyeva O.O (Ta’lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION: This article examines the impact of social media on the global spread of the English language. In the modern era, platforms such as Instagram, YouTube, and Twitter have become powerful tools not only for communication but also for language learning and dissemination. The study analyzes how social media accelerates the adoption of English as a global lingua franca, reshapes traditional language learning methods, and influences non-native speakers worldwide. The article also addresses the potential negative consequences, including the spread of informal language, grammatical errors, and the gradual displacement of native languages. The findings suggest that while social media significantly contributes to the global dominance of English, formal education remains essential in maintaining linguistic standards and preserving linguistic diversity.